Effects of the ESD protections in the behaviour of a 2.4 GHz RF transceiver: problems and solutions - Carmo, João Paulo Pereira (2008)
This paper identifies the main problems related to the Electrostatic Discharge (ESD) in submicron CMOS processes. The mitigation of this problem is made with the use of protections, in order to avoid the destruction of the internal and nput/output circuits connected to the bondingpads. In the 2.4 GHz ISM band, the parallel capacitance and the serial resistance of the ESD protections have effects in the behavior of RF transceivers. The major identified effect was the transmission range. It is proposed two strategies to solve the secondary effects, due to the protections. All the measurements and simulations were made for a 2.4 GHz RF CMOS transceiver, designed and fabricated using the UMC 0.18 µm RF CMOS process.